Feltness: On How to Practice Intimacy. (February 2021) - Springgay, Stephanie
At the invitation of Professor Carlson, this paper responds to his questions regarding the meaning, value, and the future of (post)qualitative research, and takes up some of the issues and provocations I raised with his graduate students: reciprocity, relationality, stewardship, and an ethics of care. These conditions, or what I call feltness, are deeply embedded and entwined in my doings of research, or more specifically the practice of research-creation. This feltness shifts research to become a practice of intimacy. The paper commences with a brief introduction to research-creation which is potentially a parallel methodological intervention to (post)qualitative research, as it challenges what counts as disciplinary and academic knowledge, and inherited forms of value in the institution.